Educating Local Communities on Children's Rights as an Effort to Prevent Criminal Acts - Junaidi Lubis; Leni Indrayani; Melky Suhery Simamora; Muhammad Rifky Wahyadi (Outline Journal of Community Development, 2024)
Educating local communities about children's rights is an important step in preventing crimes against children. Although there are various regulations regarding child protection, the low level of public understanding of children's rights remains a challenge. Therefore, this community service activity aims to increase public awareness of children's rights and their role in preventing violence and exploitation of children. Activities include counseling, training, social media campaigns, and mentoring parents, teachers, community leaders, as well as children and adolescents. The results of the activities show an increase in public understanding of children's rights, changes in attitudes towards child protection, and increased community participation in preventing crimes against children. Through this educational approach, the community is expected to be more sensitive to violations of children's rights and play an active role in creating a safe environment that supports children's growth and development. The evaluation showed a high level of satisfaction from participants, as well as a positive impact in strengthening child protection networks in the community.